Computer organization and design : the hardware/software interface - Patterson, David A.; Hennessy, John L. (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, Morgan Kaufmann is an imprint of Elsevier, 2014)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--Provided by publisher.
Computer abstractions and technology -- Instructions : language of the computer -- Arithmetic for computers -- The processor -- Large and fast : exploiting memory hierarchy -- Parallel processors from client to cloud.
Previous edition: 2012.
Revised edition of: Computer organization and design / John L. Hennessy, David A. Patterson. 1998.
Includes bibliographical references and index.
Keywords: Computer organization; System design -- Data processing; Computer architecture; Computer engineering; Computer interfaces